Analisis Penerapan Metode Full Costing Dalam Perhitungan Harga Pokok Produksi Untuk Penetapan Harga Jual - Lestari, Alviani; Rosita, Siti Ita; Marlina, Tri (Jurnal Ilmiah Manajemen Kesatuan, 2019)
Lemari Syukur Factory is a home industry that produces wardrobe cabinets. It determines selling price based estimation which is inappropriate. The main issue is that the company does not possess proper cost classification system in determining the cost of goods sold. This research is aimed to assist determining the cost of production as the basis for making up finished goods price using full costing method. This research includes quallitative analysis research. Data were collected through interviews and documentation and analyzed by qualitative analysis techniques. The study resulted (1) for cost of goods sold calculation, the factory charged direct material costs of Rp. 325.000.000, direct labor cost of Rp. 211.200.000 and factory overhead cost of Rp. 556,800,000. Total production cost to produce 2,196 units of cabinets in one year amounted to Rp. 1.093.000.000. The factory estimated cost of goods sold for each unit is of Rp. 497.723, and the selling price per cabinet unit is Rp. 500.000. (2) Using full costing method, the cost calculation consisted of direct material costs of Rp. 325.000.000, direct labor cost equal to Rp. 211.200.000, factory overhead fixed cost Rp. 12,042,250, and variable factory overhead cost Rp. Rp. 525.550.000. Thus, the cost of production was Rp. 1,073,792,250 for 2,196 units of cabinets. The cost of goods sold per cabinet unit is Rp. 488.976 and the selling price is Rp. 619.559. (3) The difference in cost of goods sold between full costing and the factory calculation is of Rp 8.747. While the difference between finished product price using full costing and the factory estimation is Rp 133.766.